2020
DOI: 10.1111/petr.13862
|View full text |Cite
|
Sign up to set email alerts
|

A coordinated approach to improving pediatric heart transplant waitlist outcomes: A summary of the ACTION November 2019 waitlist outcomes committee meeting

Abstract: The number of children needing heart transplantation (HT) continues to rise. 1 Although improvements in heart failure (HF) therapy, particularly durable mechanical support, have improved waitlist outcomes, much work remains to be done. Firstly, the number of children who die while waiting for a suitable donor organ remains high. Currently, around 13% children and 25% of infants on the HT waitlist will not survive to transplantation. 2 Among those who do survive to transplant, waitlist characteristics, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, a careful study of the short‐term results of this policy found that there was no decrease in overall waitlist mortality, including a lack of improvement in the waitlist mortality for Status 1A candidates with congenital heart disease 47,48 . A number of modifications have been proposed and are under consideration 48,49 …”
Section: Heart Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a careful study of the short‐term results of this policy found that there was no decrease in overall waitlist mortality, including a lack of improvement in the waitlist mortality for Status 1A candidates with congenital heart disease 47,48 . A number of modifications have been proposed and are under consideration 48,49 …”
Section: Heart Transplantmentioning
confidence: 99%
“…47,48 A number of modifications have been proposed and are under consideration. 48,49 Internationally, pediatric waitlist duration and mortality vary by country. By comparison, in the United States, the median waitlist duration for the most urgent patients is 2-3 months; in Brazil, it is 6 months; and in Japan, it is >1000 days.…”
Section: He Art Tr An S Pl Antmentioning
confidence: 99%
“…A non-exhaustive list of examples includes the following: a project to increase the rate of hospital discharge in patients on discharge-eligible continuous-flow VADs 33 ; an initiative to increase volume and parent/provider satisfaction with telemedicine visits necessitated by the COVID-19 pandemic; assessment of VAD utilization from the perspective of healthcare resource expenditures; construction of standardized rounding and discharge tools for patients hospitalized with HF, a study of patient-and parentreported outcomes (PROs) in VAD recipients; and educational modules and forums geared toward increasing donor heart utilization. 34 Common to all of these initiatives is the involvement of a multidisciplinary team including physicians, nurses, psychologists, QI spe- In a learning network, rapid dissemination of knowledge, with a particular focus on real-time release of data, is a primary aim. For ACTION, an example of this can be found in the analysis and publication of results pertaining to the use of the HeartMate 3 (HM3) ® intracorporeal continuous-flow device at ACTION centers.…”
Section: Ma Jor Ac Ti On Initiative Smentioning
confidence: 99%
“…2 Modern technologies and healthcare innovations have allowed children to live longer while awaiting a suitable heart. 3,4 Despite these advancements, there continues to be an unacceptably high rate of pretransplant mortality. 5 The Organ Procurement and Transplant Network/Scientific Registry of Transplant Recipients 2019 Annual Data Report show that 10% of pediatric transplant candidates died while awaiting transplant over a 3-y period.…”
Section: Introductionmentioning
confidence: 99%